Perencanaan Daya Dan Perbedaan Jenis Bantalan (Bearing) Pada Mesin Pengupas Kulit Kacang Tanah Kapasitas 60 Kg/Jam - Alfonso, Richard; Manurung, Charles S.P; Sihombing, Suriady; Sipayung, Pardingatan Sipayung (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2024)
Appropriate technology is technology that is right on target to be used and developed by the community. The development of technology aims to ease human work. The Indonesian state, with the majority of its population working as farmers, really needs appropriate technological innovation to increase agricultural productivity. In this case, the author highlights the low productivity of peanut farmers in Indonesia. On the other hand, the level of peanut demand is increasing from year to year, but consumer demand cannot be met due to low domestic peanut production. Therefore, this study aims to determine the power and bearing maintenance on peanut shell peeling machines using an electric motor, which uses a Tachometer measuring instrument and is carried out at the Production Laboratory of HKBP Nommensen University Medan located at JL. Sutomo No. 4 Medan. The peanut shell peeling machine is made horizontally with 1 shaft and 40 peeling rods transmitted by a V-belt and pulley using an electric motor that functions to peel peanuts to separate the seeds from the shell. By designing and designing a peanut shell peeling machine, the bearing life used in the peanut peeler machine is 3440.78 and 909.86 hours at a rotation speed of 1382 rpm and 58623.94 and 20877.55 hours at a rotation speed of 795.7 rpm. The faster the engine speed, the enumeration load received by the bearing will be lighter, the slower the engine speed, the heavier the enumeration load received by the bearing. The production capacity that can be produced by this peanut shell peeling machine is 60 kg / hour with a peeling force of 51,012 and AC motor power of 1 Hp with a rotation of 2930 rpm.